ChemInform Abstract: Tetrapyrazinoporphyrazines and Their Metal Derivatives. Part I: Synthesis and Basic Structural Information. Issue 47 (3rd November 2016) - Donzello, Maria Pia; Ercolani, Claudio; Novakova, Veronika; Zimcik, Petr; Stuzhin, Pavel A.
Abstract: Review: 307 refs.